STAD Learning Model with Ã¢â‚¬Å“Nabung Saham GoÃ¢â‚¬Â Simulation to Improve Financial Literacy - Fatimah, Siti; Rusdarti, Rusdarti; Oktarina, Nina (Universitas Negeri Semarang, 2020)
One of the aspects of literacy that students must and need to be mastered as a provision for future life is financial literacy. This study aims to develop a learning model in economics that is valid, practical, and effective to improve the financial literacy of students of SMAN 16 Semarang. The type of research was research and development (R&D) with a 4D development model which consists of define, design, develop, and disseminate stages. Due to time and cost limitations, this research only reaches the development stage with a product trial to produce the final model of learning. Model validation used expert validation technique (Delphi exercise) with two experts carried out in two stages. The data collection used expert validation sheets, teacher and student practicality sheets, test sheets, observation sheets, and questionnaires. The data obtained were analyzed quantitatively and explained descriptively in the discussion. The results of the study state that 1) The learning model meets the valid criteria, with a score of 4.05 in Stage I and Stage II with an average score of 4.32 in the very valid category 2)The results of teacher's questionnaire response have an average score of 4.30 and students have an average score of 4.31 learning model meets very practical criteria 3)The learning model has met the effective criteria. In the Paired Sample Test, there is a 2-way (t-tailed) significance value of 0.000 <0.05, which means that there is a difference between before and after the learning model carried out. The N-gain test of 0.36 is in the medium category. Thus, it means that the simulation-based STAD cooperative using Nabung Saham Go is effective in improving students' financial literacy.